2020
DOI: 10.1186/s12864-020-6584-2
|View full text |Cite
|
Sign up to set email alerts
|

Sirt2-associated transcriptome modifications in cisplatin-induced neuronal injury

Abstract: Background: Chemotherapy-induced peripheral neuropathy is not only one of the most common causes of dose reduction or discontinuation of cancer treatment, but it can also permanently decrease the quality of life of cancer patients and survivors. Notably, Sirt2 protects many organs from various injuries, including diabetic peripheral neuropathy. As demonstrated previously by our laboratory and others, the overexpression of Sirt2 can improve cisplatin-induced neuropathy, although the mechanism is still unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Furthermore, acetylation is crucial for p53-mediated ferroptosis [4]. SIRT2 exerts its biological effect by deacetylating p53 [8,25]. In the present study, our findings suggest that the SIRT2 inhibits ferroptosis by deacetylating and downregulating p53.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, acetylation is crucial for p53-mediated ferroptosis [4]. SIRT2 exerts its biological effect by deacetylating p53 [8,25]. In the present study, our findings suggest that the SIRT2 inhibits ferroptosis by deacetylating and downregulating p53.…”
Section: Discussionsupporting
confidence: 62%
“…Some evidence states that SIRT2 accumulates in the nuclei of dorsal root ganglion sensory neurons and the protection of peripheral neurons against cisplatin is possible through its activation [ 161 ]. Zhao et al [ 162 ] described that SIRT2 may have an impact on the pathways like MAPK, TNF, or the cytokine-cytokine interaction, which was a result of RNAseq technique usage in cultured rodent neurons. Cisplatin-induced changes were proven to depend on SIRT2 status, with 783 affected genes measured in SIRT2-deficient cells and 227 affected genes in the SIRT-2-expressing cells, therefore indicating SIRT2 presence to regulate the response to cisplatin [ 162 ].…”
Section: Sirtuinmentioning
confidence: 99%
“…Zhao et al [ 162 ] described that SIRT2 may have an impact on the pathways like MAPK, TNF, or the cytokine-cytokine interaction, which was a result of RNAseq technique usage in cultured rodent neurons. Cisplatin-induced changes were proven to depend on SIRT2 status, with 783 affected genes measured in SIRT2-deficient cells and 227 affected genes in the SIRT-2-expressing cells, therefore indicating SIRT2 presence to regulate the response to cisplatin [ 162 ]. To the best of authors’ knowledge, no clinical trials investigating the feasibility of using SIRT2 as an ameliorative factor in CIPN have been performed to this day.…”
Section: Sirtuinmentioning
confidence: 99%
“…Besides revealing direct effects on the immune cells and cytokines production, OHP and CDDP may affect inflammatory compartment modulating gene expression. In particular, it has been reported that CDDP may affect the expression of genes implicated in neuroinflammatory processes such as TNF-α and cytokine-cytokine interactions pathways in cultured rat sensory neuron-like cells ( 32 ). In agreement with these findings, the transcriptome analysis of lumbar DRG of CDDP-treated mice revealed changes in the expression of genes involved in both neuronal damage and inflammatory processes ( 33 ).…”
Section: Introductionmentioning
confidence: 99%